Beyond physical fitness: Pre-to-post hematological and physical fitness changes during an eight-week multi-component exercise program in sedentary adults aged 30–45 years - Yasin Demircan; Vedat Ayan; Selami Yüksek; Fatih Gür; Burak Kural; Halit Şar (PLoS ONE, 2026)
This exploratory study aimed to examine pre-to-post changes in physical fitness and selected hematological parameters during an 8-week multi-component exercise program in sedentary adults. The study used a single-group pre-test/post-test quasi-experimental design to describe temporal changes within the same participants. Thirty-six sedentary volunteers (15 females and 21 males) aged 30–45 years completed a multi-component program including cardiorespiratory endurance, strength, balance, and flexibility exercises for 45–50 minutes per session, 3 days per week, for 8 weeks. Paired-samples t-tests were used to compare pre-test and post-test measurements. Body weight and body mass index decreased, whereas estimated VO 2 max, vertical jump, flexibility, speed, agility, and balance performance showed statistically significant pre-to-post changes (all p < 0.001). Significant increases were also observed in hemoglobin, hematocrit, erythrocyte, leukocyte, and platelet values (all p < 0.001), whereas MCV and MCH did not change significantly (p > 0.05). Participation in the program coincided with favorable changes in body composition and physical performance and with measurable changes in selected hematological parameters. However, the absence of a control group and the lack of direct assessment of plasma volume, hydration status, erythropoietin, iron status, and hemoglobin mass preclude causal and mechanistic conclusions. The hematological findings may partly reflect hemoconcentration, plasma-volume shifts, or other physiological variation and should therefore be interpreted cautiously.